Comparisons and validations on MIMO channel simulation models - Xiongwen ZHAO; Bo GAO (Dianxin kexue)
WINNER and COST2100 channel models are geometry based statistical models，they are the most important channel models for MIMO（multi-input multi-output）system simulations in the fourth generation（4G）radio systems. Due to different physical mechanism advantages for WINNER and COST2100 models，there is almost no work available for the comparative studies between the two channel models and effectiveness and agreement in a specific scenario. The channel simulation and measurement studies for the two channel models in indoor environment was focused on. In the line-of-sight（LOS）and non-line-of-sight（NLOS）cases，the power-delay-profile （PDP），Ricean factor，channel capacity，rms delay and rms angular spread were simulated using the two channel models and measurement data. The comparative studies between the simulation and measurement results are performed to test the effectiveness and agreement of the two models in a practical application environment.